Whole-genome sequencing and de novo assembly of a 2019 novel coronavirus (SARS-CoV-2) strain isolated in Vietnam - Lam, Le Tung; Hieu, Nguyen Trung; Trang, Nguyen Hong; Thuong, Ho Thi; Linh, Tran Huyen; Tien, Luu Thuy; Thao, Nguyen Thi Ngoc; Loan, Huynh Thi Kim; Quang, Pham Duy; Quang, Luong Chan; et al. (Vietnam Journal of Biotechnology, 2020)
The pandemic COVID-19 caused by the virus SARS-CoV-2 has devastated countries worldwide, infecting more than 4.5 million people and leading to more than 300,000 deaths as of May 16th, 2020. Whole-genome sequencing (WGS) is an effective tool to monitor emerging strains and provide information for intervention, thus help to inform outbreak control decisions. Here, we reported the first effort to sequence and de novo assemble the whole genome of SARS-CoV-2 using PacBio’s SMRT sequencing technology in Vietnam. We also presented the annotation results and a brief analysis of the variants found in our SARS-CoV-2 strain, which was isolated from a Vietnamese patient. The sequencing was successfully completed and de novo assembled in less than 30 hours, resulting in one contig with no gap and a length of 29,766 bp. All detected variants as compared to the NCBI reference were highly accurate, as confirmed by Sanger sequencing. The results have shown the potential of long read sequencing to provide high quality WGS data to support public health responses and advance understanding of this and future pandemics.